Burnout prevalence and correlates amongst Colombian dental students: The STRESSCODE study (2015)
Introduction: Accumulating evidence amongst dental students indicates an alarming prevalence of stress, which can precipitate the development of burnout - a state of mental or physical exhaustion and disengagement. Understanding individual and educational correlates of burnout is necessary for its prevention. The aims of this study were to determine the prevalence of burnout amongst a large sample of Colombian dental undergraduates and investigate its psychosocial and educational correlates. Materials and methods: Survey data collected from 5647 students participating in the Stress in Colombian Dental Education study were used for this analysis. Burnout was measured using the Maslach Burnout Inventory-Student Survey (MBI-SS). Covariates included participants' socio-demographic characteristics and perceived stress, as well as educational environment factors. Descriptive, bivariate and multivariate methods based on multilevel mixed-effects logistic regression modelling were used for data analysis. Results: Seven per cent of the students surveyed met the criteria for burnout. The prevalence of burnout was higher amongst upper classes, older and married students, those who reported not having passed all required courses and not having dentistry as their first career choice, as well as students in public institutions and those with large class sizes. Moreover, students' perceived stress in the domains of workload and self-efficacy was significantly and positively associated with burnout. Conclusions: Both personal and educational environment characteristics were found to be associated with burnout. Irrespective of these factors, students' perceived stress with regard to workload and self-efficacy was a strong influence on burnout and its alleviation may be a promising avenue to prevent psychological morbidity. © 2015 John Wiley & Sons A/S.